(untitled) (Revista LIDER, 2021)
The process of sugar cane industrialization in western Venezuela arose due to the vision and the efforts of a Zulia group by their eagerness of profit and wealth accumulation. They used their knowledge and sophisticated technology to increase sugar production and to compete in national and international markets. Starting in the Seventeenth century, after the appearance of the first cane tillages, formerly for the production of unrefined brown sugar and rum, and passing through some adjustment periods, until the arrival of the Twentieth century, this industry developed due to the advantageous conditions of the Venezuelan agrarian structure. Due to large-scale production, particularly in the Sucre district of Zulia state, towards the south of Maracaibo lake, this merchandise became a product for export. Since 1912, the ”Union Agrícola” company deepened its exploitation, concentrating the land in a few hands, and founded the first Sugar Factory established in the country: The Zulia State Sugar Factory. This initiative joined local and regional private capitals with national capitals. The sugar enterprise constituted by the factories “El Banco” y “Central Sucre” expanded the cane landscape and incorporated Creole and Afro-descendant workers.